Features of calculation of two-case vacuum-evaporating crystallization - G. A. Nosov; V. I. Sorokina; Yu. O. Terekhova (Тонкие химические технологии)
A technique for calculating a two-case vacuum-evaporating crystallization installation was considered. The first case of the installation it is used for concentrating the initial solution by its evaporation. The second case is used for evaporating crystallization. Thus, secondary steams of the evaporating device are used for crystallizer heating.